O trágico, o futebol e o erotismo: a presença de uma tríade temática nas capas dos jornais populares do Brasil e Portugal - Rodrigo Daniel Levoti Portari (2013)
This research has focused primarily on popular journalism and the recurring themes on their covers: the tragic, football and eroticism. Together these themes articulate what we call thematic triad and are responsible for presenting reconstructions world for their readers. In order to establish how this phenomenon occurs in the context of popular journalism and check dates and distances between the subjects and their representations to the Portuguese-speaking countries, was elected two popular newspapers for a comparative study, with the Super Notícia, of Belo Horizonte, and the Jornal de Notícias, of Porto (Portugal).